An Overview Of Bureau Of Mines Communications Research - Harry Dobroski; John Durkin (The National Institute for Occupational Safety and Health (NIOSH))
This paper presents a general overview of the Bureau of Mines' programs in the areas of operational and post-disaster communications. These programs encompass both hardware developments and system evaluations. Topics discussed include a new visual paging system compatible with existing pager phone lines, a means of modifying commercially avail able pager phones to permit selective paging and message leaving, a multiplexed telephone system that uses twisted shielded pair and requires no central control, medium frequency hardware developments, and a manual for mine communications. Research has continued in the area of post-disaster location and communications. This research is based on seismic and electro- magnetic techniques. Each has been extensively studied and field tested to better understand its ability to perform effectively. A brief description is given of the post-disaster program. Results are promising and provide insight into future areas of research.